Analysis of Synchronous Generator Operation in Ship Electrical Systems: A Literature Review - Mujiono, Restu; Kurniawan, Teguh (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2026)
Shipboard electrical systems operate as isolated microgrids, with synchronous generators serving as key components for maintaining power continuity, voltage and frequency stability, and preventing blackouts. However, the evolution toward AC/DC hybrid architectures, energy storage integration, intelligent Power Management Systems (PMS), and data-driven protection has altered the technical requirements for generator operation. This article presents a critical literature review—conducted according to the PRISMA workflow—on synchronous generator operation in modern shipboard electrical systems. A structured search was performed across IEEE Xplore, ScienceDirect, MDPI, SpringerLink, and Google Scholar. The review compares strategies for voltage regulation, governor- and droop-based frequency control, synchronization and parallel operation, protection coordination, dynamic stability, and PMS functions. Mathematical formulations—such as the swing equation, power-angle relationship, active and reactive power control, droop characteristics, and excitation response—are also discussed to underpin the analysis. Synthesis of the findings indicates that the reliability of shipboard generators cannot be assessed solely through steady-state parameters; rather, it requires analysis of the interactions between excitation systems, governors, synchronization conditions, protection schemes, PMS optimization, transient stability, and maintenance practices. Research gaps identified include the experimental validation of AI-based excitation control, cyber-resilient PMS, generator protection in AC/DC hybrid grids, and digital twin-based diagnostics. This article proposes a comparative technical framework for analyzing synchronous generators within integrated shipboard electrical architectures